Հոլովական տեղաշարժեր Գրիգոր Խլաթեցու «Բնագրական նշմարներ»-ում - Ծատուրյան, Տ. Տաճատ Վարդապետ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Несмотря на то, что Григор Хлатеци жил и творил в конце XIV — начале XV вв., тем не менее, при написании текстов на среднем армянском языке в значительной степени был связан с V в., в качестве источника имея для себя классический древнеармянский язык (грабар). Общность с древнеармянский в значительной степени чувствуется в системе падежей, где некоторые склонения внутреннего наклонения, морфема «к» (ք) во множественном числе и т. д., по своему строению они достигают V в. При всем этом есть много общего и с ашхарабаром (современным армянским): они связаны схожестью падежных окончаний, в способах образований множественного числа и склонениях имен существительных и местоимений. Although Grigor of Khlat lived and worked in the late 14th and early 15th century, he was greatly attached to the 5th century while writing in the Middle Armenian language, having as an origin the Classical Armenian language. The similarities with the Classical Armenian language are very significant in the case system, in which some declension forms, “ք” plural ending, etc., with their structure date back to the 5th century. Despite all this, they have a lot in common with the Modern Armenian language. They are related to case endings, plural forms specific to the Modern Armenian language, approach of nominal and pronominal cases.
Keywords: Բանասիրություն; Քննադատություն; Լեզվաբանություն